Occurrence of mesothelial/monocytic incidental cardiac excrescences in material from open-heart procedures: case reports and literature review - Vitor Gabriel Ribeiro Grossi; Karen Lee; Léa Maria Demarchi; Jussara Bianchi Castelli; Vera Demarchi Aiello (University of São Paulo, 2018)
Mesothelial/monocytic incidental cardiac excrescences (MICE) are unusual findings during the histological analysis of material from the pericardium, mediastinum, or other tissues collected in open-heart surgery. Despite their somewhat worrisome histological appearance, they show a benign clinical course, and further treatment is virtually never necessary. Hence, the importance of recognizing the entity relays in its differential diagnosis, as an unaware medical pathologist may misinterpret it for a malignant neoplasm. Other mesothelial and histiocytic proliferative lesions, sharing very close histological morphology and immunohistochemistry features with MICE, have been described in sites other than the heart or the mediastinum. This similarity has led to the proposal of the common denomination "histiocytosis with raisinoid nuclei." We report three cases from the pathology archives of the Heart Institute of São Paulo University (Incor/HC-FMUSP), diagnosed as "mesothelial/monocytic incidental cardiac excrescence," with immunohistochemical documentation, and provide a literature review of this entity.